Team Games Tournament Assisted by Math Journal as An Effort to Improve Students’ Numeracy Skills (APPLICATION: Applied science in Learning Research, 2025)
The research aims to improve students' numeracy skills by applying Team Games Tournament (TGT) type cooperative learning assisted by Math Journal. This research used a quantitative approach with a pre-experimental design method of one group pretest-posttest type. The research subjects were students of Grade VIII of SMP Negeri 2 Perak Jombang. The research has used instruments in the form of questions that consist of pre-test and post-test, questionnaires as supporting data and TGT teaching modules. The test instrument was supported by the results of a student questionnaire. The data analysis technique used is hypothesis testing using paired samples t-test. Based on the results of the paired sample t-test, the significance value is 0.000. The significance value obtained is 0.000